The Aesthetics & Ethics of Zapin Siak in Riau Province - Ainuddin Ainuddin; Daryusti Daryusti (LANGGAM: International Journal of Social Science Education, Art and Culture, 2026)
This study aims to examine the aesthetic and ethical values in Zapin Siak art in Riau Province. The study uses a qualitative approach with observation, interviews, and documentation techniques on artists and Zapin supporters. The results show that the aesthetic values of Zapin Siak are reflected in the harmony of movement, musical accompaniment, simple costumes, and balanced performance patterns, reflecting the gentle and orderly character of Malay culture. Ethical values are seen in the controlled posture of the dancers, the rules of pairing that maintain modesty, and the lyrics that contain moral and religious messages. Aesthetics and ethics in Zapin Siak are interrelated and form a complete cultural identity. However, modernization has influenced the form of performance and the meaning of cultural values, so preservation efforts are needed through an understanding of cultural meaning, not only through performance.